Impact of Magnetic Field Strength and Receiver Coil in Ocular MRI: A Phantom and Patient Study - Erb-Eigner, K.; Warmuth, C.; Taupitz, M.; Willerding, G.; Bertelmann, E.; Asbach, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: Generally, high-resolution MRI of the eye is performed with small loop surface coils. The purpose of this phantom and patient study was to investigate the influence of magnetic field strength and receiver coils on image quality in ocular MRI.Materials and Methods: The eyeball and the complex geometry of the facial bone were simulated by a skull phantom with swine eyes. MR images were acquired with two small loop surface coils with diameters of 4 cm and 7 cm and with a multi-channel head coil at 1.5 and 3 Tesla, respectively. Furthermore, MRI of the eye was performed prospectively in 20 patients at 1.5 Tesla (7 cm loop surface coil) and 3 Tesla (head coil). These images were analysed qualitatively and quantitatively and statistical significance was tested using the Wilcoxon-signed-rank test (a p-value of less than 0.05 was considered to indicate statistical significance).Results: The analysis of the phantom images yielded the highest mean signal-to-noise ratio (SNR) at 3 Tesla with the use of the 4 cm loop surface coil. In the phantom experiment as well as in the patient studies the SNR was higher at 1.5 Tesla by applying the 7 cm surface coil than at 3 Tesla by applying the head coil. Concerning the delineation of anatomic structures no statistically significant differences were found.Conclusion: Our results show that the influence of small loop surface coils on image quality (expressed in SNR) in ocular MRI is higher than the influence of the magnetic field strength. The similar visibility of detailed anatomy leads to the conclusion that the image quality of ocular MRI at 3 Tesla remains acceptable by applying the head coil as a receiver coil.Key Points:Citation Format:
Keywords: eye; MR-imaging; technical aspects